2021
DOI: 10.35631/jistm.623001
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Nationhood Knowledge in Malaysian Studies Courses: A Conveyance for National Unity and an Integration of University Students’ Identity

Abstract: This paper debates the relevance of knowledge of nationhood as a conveyance for national unity identity and integration of university students’ self-identity in addressing the issues and challenges of the Covid-19 post-pandemic era. In dissecting the significance of university student’s understanding of the Malaysian Studies course, the thrust of this discussion perspective works on the two-pronged objectives of (1) identifying the relevance of national unity identity issues of the younger generation, and (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Therefore, students should always maintain behavior and integrate human values into themselves, making it a life rule until it becomes a habit to be carried into the world of work. Hence, the national subjects covering customs, etiquette, and civilizational culture to shape a pure identity and a high spirit of unity are highly relevant (Othman et al, 2021c).…”
Section: Discussion: Issues and Challenges Issue 1: The Need For Stud...mentioning
confidence: 99%
“…Therefore, students should always maintain behavior and integrate human values into themselves, making it a life rule until it becomes a habit to be carried into the world of work. Hence, the national subjects covering customs, etiquette, and civilizational culture to shape a pure identity and a high spirit of unity are highly relevant (Othman et al, 2021c).…”
Section: Discussion: Issues and Challenges Issue 1: The Need For Stud...mentioning
confidence: 99%
“…In a study of Chinese international students, Tian et al (2020) 3 found that university rankings significantly influenced students' choices of universities in the UK, but not in Australia. Similarly, in a study of Malaysian students, Othman and Mokhtar (2019) 4 found that university rankings were not a significant factor in university selection.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Students are the backbone of a country's modernization efforts and the hope for future progress. As a result, their thoughts and attitudes toward the subject of national unity have a direct effect on the society (Othman et al, 2021). In universities, students gain the willingness and competence to live in a multicultural society and provide the framework for a flexible adaptation of intercultural tolerance (Tregubova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%